Timor-Leste - Oecusse Economic and Trade Potential : Overview of Oecusse Today and Long Term Potential - World Bank Group (World Bank, Washington, DC, 2016)
This report responds to a request from the Government of Timor-Leste (GoTL) and Dr. Mari Alkatiri. The request was for World Bank assistance to collaborate on a range of studies relating to opportunities in the special economic zone, including community development, trade and competitiveness, and regional integration. The analysis builds on a situation analysis prepared by the Zona Especial de Economia Social de Mercado (ZEESM) authority in March 2014. The transfer of significant responsibility for Oecusse’s development to the ZEESM authority, reflects a political rapprochement and collaboration between Prime Minister Xanana Gusmao and Dr. Alkatiri. The report is in two volumes. Volume one presents an overview of Oecusse’s current state in chapter one with analysis of living standards, economic activity including trade, and current constraints. Chapter two analyzes Oecusse’s phased economic potential through a range of phase one development interventions focusing on agriculture, and considers the pre-requisites for developing an SEZ in Oecusse. Volume two contains more comprehensive background chapters with full analysis of living standards in chapter three, agriculture in chapter four, transport corridor in chapter five, and migration in chapter six.